Optimizing Floral Business Sales in Bukittinggi and Surrounding Areas: A Case Study of Eunoia.um Flower Shop's Marketing Strategies - Rahma Maria Sanopa; Zuripal Zuripal (Jurnal Mirai Management, 2023)
In the dynamic landscape of business, effective marketing strategies are vital for sustaining and expanding enterprises. This research focuses on the importance of marketing strategies in the context of "Toko Bunga Eunoia.um," a florist business in Bukittinggi. The study employs a comprehensive approach, integrating internal and external analyses to identify the strengths, weaknesses, opportunities, and threats (SWOT) faced by the business. The SWOT analysis leads to the formulation of alternative marketing strategies, encompassing product development, pricing incentives, promotional activities, and workforce enhancement. The research emphasizes the significance of social media platforms, such as Facebook, Instagram, and TikTok, in amplifying the visibility of the florist business and reaching a wider audience. The findings underscore the critical role of marketing in business success, particularly for small and medium enterprises (UMKM) operating in a competitive environment. Recommendations include intensifying marketing activities based on the prioritized strategies, organizing engaging events to increase local awareness, and implementing the formulated strategies with effective communication to all employees. The ultimate goal is to strengthen the marketing efforts of "Toko Bunga Eunoia.um," enhance its community presence in Bukittinggi, and ensure sustainable business growth. Keywords: Marketing Strategies, SWOT Analysis, Florist Business, Small and Medium Enterprises, Business Growth